The bridge that divides: local perceptions of the connected state in the Kyrgyzstan–Tajikistan–China borderlands. Issue 3 (2nd July 2016) - Parham, Steven
ABSTRACT: The collapse of the Soviet Union in 1991 brought profound changes to the borderlands of Kyrgyzstan, Tajikistan and Xinjiang. In eastern Kyrgyzstan and Tajikistan's Gorno-Badakhshan region, present-day weaknesses in territorial control of the post-Soviet state's edges are directly wedded to borderlanders' memories of Soviet-era practices of bordering, perceived locally as both systemically stronger and cognitively more beneficial to local lifeworlds than contemporary 'Chinese penetration'. Across the border in Xinjiang, a formerly distant state has been brought into borderlanders' locales and inscribed into everyday lifeworlds through novel manifestations of the state, which significantly affect cross-border interaction. By comparing how borderlanders on both sides of this frontier themselves choose to characterize border processes between 'their' states in the initial two decades of connections to Xinjiang, I explore how and why Kyrgyz and Tajik/Pamiri borderlanders voice strong opinions about what it is they feel has changed in these administrative-territorial homelands. Based on extensive ethnographic fieldwork on both sides of this frontier, I argue that the gradual bridging of this formerly sealed border has led to neither the development of a new trans-frontier identity nor locally established trans-frontier networks but, instead, reconfirmed borders between China and Central Asia.